High-strength marine engineering steel with high ductility and resistance to seawater corrosion fatigue and its manufacturing method
Through the composition design of low C+"Cr-Cu-Mo" alloying and V-N microalloying, combined with secondary heating rolling and controlled cooling technology, a 360Mpa grade steel plate with high ductility and resistance to seawater corrosion fatigue was prepared, and the solution was solved The service safety and stability of steel used in marine engineering in harsh environments has achieved efficient improvement in steel plate performance.
Patent Information
- Application Number
- CN202311620259.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The existing marine engineering steel is difficult to take into account high ductility, corrosion resistance and low temperature toughness in harsh marine environments, resulting in insufficient service safety and stability, and the existing process is complex, low production efficiency and high cost.
The composition design of low C+"Cr-Cu-Mo" alloying + V-N microalloying is adopted, combined with secondary heating controlled rolling and cooling processes, to regulate the microstructure and grain size of the steel plate, and the preparation is highly ductile and 360Mpa grade steel plate that resists seawater corrosion fatigue.
The steel plate has achieved high ductility (tensile elongation ≥33% after break), high strength (yield strength ≥360MPa), low-temperature impact toughness (-40℃ impact work ≥250J) and seawater corrosion fatigue resistance (corrosion fatigue life is More than 2.5 times that of conventional steel plates) are suitable for long-term service conditions of marine engineering equipment.
Smart Images

Figure CN117467897B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal materials, and in particular relates to a high-strength marine engineering steel with high ductility and resistance to seawater corrosion fatigue and a manufacturing method thereof. Background Art
[0002] The particularity of the application environment of marine engineering has always placed high requirements on the service safety of marine equipment and structural materials. In recent years, as the offshore industry is gradually transforming and upgrading to the marine industry, the service environment of marine equipment has become increasingly complex and harsh. Not only does it require marine engineering steel to have good strength, but it also specifically requires steel plates to have high ductility and ultra-low temperature toughness to cope with sudden accidents and operational safety in severe sea conditions that ships and marine engineering equipment may encounter. The American ABS classification society has currently incorporated high ductility performance indicators into the relevant specifications "Material requirements for higher-ductility hull structural steel plates and sections". Its purpose is to allow the steel plate to absorb the energy of the collision when the ship, marine engineering equipment and structure collide, so that it is not easy to cause structural instability, thereby improving the service safety of the equipment. Japan's Nippon Steel and Sumitomo Metal have developed such marine engineering steel plates with high ductility and anti-collision functions ("NSafe-Hull" series), which are currently in the application stage. At present, my country has not formed a systematic research and large-scale application of such steel plates.
[0003] On the other hand, corrosion fatigue is a key factor affecting the stability of long-term service of marine equipment and structures. The maximum loading stress amplitude is often less than the material yield limit, and there is no sign before failure. In the corrosion fatigue process, there are two basic damage modes, one is corrosion damage caused by corrosive media; the other is fatigue damage caused by alternating loads. These two material damage modes are not simply superimposed in this process, but there is an obvious coupling effect. In particular, for marine engineering steel, which is subjected to the alternating effects of low temperature, chloride ions, dry-wet cycles, wind and waves, and sea ice loads in its service environment for a long time, the risk of failure of the material due to corrosion fatigue in such a harsh environment will increase dramatically.
[0004] For a long time, people have paid more attention to strength and toughness indicators in the design and manufacturing of marine engineering steel, but paid less attention to implicit safety service indicators such as material ductility and corrosion fatigue resistance. However, with the deepening of human exploration of marine resources, marine engineering applications are developing towards deep sea and offshore. The long-term service safety and stability brought by high ductility and corrosion fatigue resistance will surely become an inevitable trend in the future demand for marine engineering steel.
[0005] Public reports of related patents:
[0006] The invention with publication number CN110846554A discloses a method for manufacturing a high-ductility EH32 grade marine engineering steel and steel plate. The patent adopts a composition design scheme with alloy reduction, does not add high-priced metals and micro-alloying elements, and achieves high ductility and low-temperature toughness of the steel plate through a three-stage controlled rolling + controlled cooling TMCP process. However, since the three-stage rolling process requires two intermediate billets to be heated, the process is relatively cumbersome and the production efficiency is low. The corrosion fatigue performance of the steel plate was not evaluated.
[0007] The invention with publication number CN108517462A proposes a high-ductility EH40 grade ship plate steel and its preparation method. The patent is designed with low carbon and micro-alloy strengthening components, and adopts two-stage rolling plus water cooling-air cooling-water cooling three-stage cooling. The production process of this technology is complex, the control capability of the cooling equipment is high, and the process window is narrow. The corrosion fatigue performance of the steel plate has not been evaluated.
[0008] The invention with publication number CN110714171A discloses a high-ductility EH420 grade ship plate steel and its production method. The patent uses the TMCP method of low carbon plus Nb and Ti microalloy strengthening combined with two-stage rolling and two-stage cooling, and uses ultra-fast cooling technology with a cooling rate of 60℃ / s to obtain a composite structure of soft phase ferrite and hard bainite. However, this technology is difficult and it is difficult to achieve the required cooling rate conditions in actual industrial production. There are also limitations on the thickness of the steel plate. The steel plate has not been evaluated for corrosion fatigue performance.
[0009] The invention with publication number CN112899570A discloses a corrosion-resistant fatigue steel for engineering use. The steel is based on the main elements of E690 steel (C 0.04-0.07%, Si 0.20-0.26%, Mn 1.45-1.60%, P≤0.01%, S≤0.015%, Cr0.44-0.50%) to ensure comprehensive mechanical performance requirements. The initiation and propagation of corrosion fatigue cracks are suppressed by adding and regulating the characteristic elements of Cu, Ni, and Sb to meet the requirements of corrosion-resistant fatigue design of engineering steel. The corrosion fatigue strength is improved by up to 52%, but the low-temperature toughness of the steel is not evaluated.
[0010] The invention with the publication number CN114836694A discloses a marine seawater corrosion fatigue resistant ultra-high strength steel and a manufacturing method, which uses low carbon and adds Cu, Ni, Cr, Mo, Sb, Sn elements to improve the corrosion resistance of the steel, and improves the fatigue performance of the steel by adding Si, Nb, VN elements. Through the interaction between the elements, the initiation and expansion of steel corrosion fatigue cracks are inhibited, and a three-stage rolling process is used to finally obtain a steel with good seawater corrosion fatigue resistance. Its corrosion fatigue life is 1.5 times that of conventional steel plates, and the elongation of the steel plate after tensile fracture ranges from 22% to 27%. However, this technology focuses more on the corrosion aspect in the corrosion fatigue performance of steel. By adding a large variety of corrosion-resistant characteristic elements to improve the corrosion resistance of steel, not only the difficulty and cost of smelting are increased, but also the solid solution and precipitation of more alloy elements will cause lattice distortion or form potential crack sources, thereby adversely affecting the fatigue and elongation performance of the steel.
[0011] The invention with publication number CN114959418A discloses a high-strength marine seawater corrosion fatigue resistant steel and a manufacturing method. The steel is low-carbon and alloy elements such as Cu, Ni, Cr, Sb, and Sn are added to improve the corrosion resistance of the steel. The fatigue performance of the steel is improved by adding elements such as Si, Nb, and VN. The purity of the steel is improved by adding rare earth elements. The initiation and expansion of steel corrosion fatigue cracks are inhibited through the interaction between the elements. The steel is rolled in a two-stage rolling process of low-speed and high-pressure reduction in the first stage and high-speed and high-pressure reduction in the second stage. The steel plate structure finally obtained is refined equiaxed ferrite + granular bainite + a small amount of pearlite structure, the ferrite content is ≥85%, and the grain size is 10-20μm. The steel plate has good seawater corrosion fatigue resistance, which is 1.5 times that of conventional steel plates, and the tensile elongation of the steel plate is in the range of 26% to 32%. However, this technology also focuses on improving the corrosion resistance of steel by adding a wide variety of corrosion-resistant characteristic elements and rare earth elements, which increases the difficulty and cost of smelting, and also has an adverse effect on the fatigue and elongation properties of steel.
[0012] The invention with publication number CN111014292A discloses a method for improving the production efficiency of thick plates of a single-stand rolling mill, by directly cooling the intermediate billet after the first heating and rolling, and then heating and rolling for the second time, and then directly rolling to the finished product thickness after the second heating to the target temperature. The method of directly cooling the intermediate billet and then heating and rolling again saves the cooling time of the intermediate billet, which can significantly improve the efficiency of the rolling mill and thus greatly increase the mill hourly output. However, this method increases the consumption of energy and industrial water due to the increase of the heating and cooling process in the process path, and the extent of the improvement in production efficiency remains to be discussed. Summary of the invention
[0013] The object of the present invention is to overcome the above-mentioned problems and shortcomings and to provide a high-strength marine engineering steel with high ductility, seawater corrosion fatigue resistance and a manufacturing method thereof, which has comprehensive performance that can meet the long-term service conditions of marine engineering equipment, with a tensile elongation after break ≥33%, an impact energy of -40°C ≥220J, and an NDTT temperature ≤-50°C.
[0014] The object of the invention is achieved in this way:
[0015] The present invention adopts the composition design of low C + "Cr-Cu-Mo" alloying + VN microalloying, combines the secondary heating controlled rolling and controlled cooling process to control the microstructure and grain size of the steel plate, and obtains a 360Mpa grade steel plate with high yield rate, stable strength and toughness, and especially resistance to seawater corrosion fatigue and high ductility. Compared with the above-mentioned public patents, this patent prepares a steel plate with seawater corrosion fatigue resistance, high ductility and low-temperature toughness suitable for the field of marine engineering. Its comprehensive performance can meet the long-term service conditions of marine engineering equipment, with a tensile elongation of ≥33%, an impact energy of ≥220J at -40℃, and an NDTT temperature of ≤-50℃.
[0016] A high-strength marine engineering steel with high ductility and resistant to seawater corrosion fatigue. The steel has the following components by weight percentage: C: 0.045%-0.075%, Si: 0.35%-0.55%, Mn: 1.0%-1.40%, Cr: 2.50%-3.50%, Cu: 0.20%-0.50%, Mo: 0.25%-0.35%, V: 0.020%-0.039%, N: 0.017%-0.025%, Ca: 0.002%-0.005%, P: ≤0.01%, S: ≤0.002%, Als: 0.02%-0.05%, and the rest is Fe and unavoidable impurities.
[0017] The marine engineering steel has a microstructure of ferrite+bainite, wherein the volume percentage of ferrite is 85% to 95%, and the average grain size of ferrite is 8.0 to 12.0 μm.
[0018] The offshore steel plate has a yield strength of ≥360MPa, a tensile strength of 490-630MPa, a Charpy impact energy of ≥250J at -40°C, a zero plastic transition temperature (NDTT) ≤-50°C, a tensile elongation after fracture of ≥33%, a maximum elongation of ≥28%, a steel plate thickness of 20-50mm, and a seawater corrosion fatigue resistance of more than 2.5 times that of conventional steel plates.
[0019] The reasons for the composition design of the present invention are as follows:
[0020] C: is a necessary element to ensure strength. It has a significant effect on improving the strength of steel through solid solution strengthening and precipitation strengthening. However, too high C content has a negative impact on the ductility, low temperature toughness and fracture toughness, weldability, fatigue resistance and corrosion resistance of steel. Too low C content will lead to high austenite crystal mobility, affect the uniform refinement of TMCP process organization, and easily form mixed crystal organization. Therefore, from the perspective of product performance, it is preferred that the C content be controlled at C: 0.045% to 0.065%.
[0021] Si: It is the main deoxidizing component in the steelmaking process. Si in the form of solid solution will increase the strength while also increasing the ductile-brittle transition temperature, elastic limit and fatigue strength. In order to obtain a sufficient deoxidation effect, it must contain more than 0.10%. However, too high an upper limit will reduce the toughness of the base material and the weld, and have an adverse effect on the surface quality of the steel. Therefore, the preferred Si content is 0.35% to 0.55%.
[0022] Mn: Mn is an essential element to ensure the strength and toughness of steel. With the increase of Mn content, the strength of steel increases significantly. 1% Mn can increase the tensile strength by about 100MPa. In addition to improving strength and toughness, it also has the effect of expanding the austenite phase, reducing the temperature of Ac1, Ac3, Ar1, Ar3 points, and refining ferrite grains. However, Mn is easy to segregate in steel, and it is easy to segregate at 1 / 4 and 1 / 2 thickness of medium and thick steel plates, resulting in a strong decrease in low-temperature toughness and even impact fracture delamination. More importantly, with the increase of Mn content, the corrosion resistance of the steel plate will drop sharply. Therefore, considering the material mechanics and corrosion resistance, it is preferred that the Mn content be controlled in the range of 1.0% to 1.40%.
[0023] Cr: Cr is an effective element to improve the corrosion resistance of steel. The addition of Cr in steel has a significant effect on the electrochemical process of steel. Cr can inhibit the anodic dissolution process in the electrochemical process, and the corrosion potential of the steel matrix shifts positively. The higher the amount of Cr added, the more obvious the inhibitory effect on the anodic process. On the one hand, Cr can form Cr2O3 and Cr(OH)3 products with better stability and corrosion resistance in the rust layer; on the other hand, Cr can promote the formation of α-FeOOH in the rust layer, and a part of it will be doped in α-FeOOH and Fe3O4 to form thermodynamically more stable α-(Fe,Cr)OOH and FeCr2O4. Under the combined effect of the two, the stability and protection of the rust layer of Cr-containing steel are greatly improved. The Cr-containing products in the rust layer can improve the original loose and porous network structure of the rust layer, provide more nucleation sites, and the rust particles gradually spheroidize and refine, which is conducive to the subsequent close agglomeration and fusion between particles, and the defects in the rust layer are reduced. With the extension of time, the structure of the rust layer gradually densifies, which can effectively hinder the penetration of corrosive Cl- ions in seawater. In addition, Cr is also an effective element for improving the strength of steel plates, but excessive Cr may cause a decrease in welding performance, so the present invention controls the Cr content to 2.5% to 3.5%.
[0024] Cu: Cu is an essential element to improve the corrosion resistance of steel in marine environment. During the corrosion process of steel, it will be enriched in the inner rust layer in the form of CuO, which can well isolate corrosive media, reduce the promoting effect of chloride ions on corrosion, and increase the polarization resistance of steel, resulting in enhanced protection of the rust layer, thereby improving the corrosion resistance of steel in marine environment. In terms of mechanical properties, Cu can improve the strength of steel plates and has little effect on the low-temperature toughness of steel plates; but when too much Cu is added, fine and dispersed ε-Cu precipitation will occur during hot rolling and normalizing treatment (the solid solubility of Cu in ferrite is about 0.45%), which will damage the low-temperature toughness of the steel plate, and may also cause copper embrittlement, ingot cracks, liquid precipitation and other defects. Therefore, considering the material mechanics and corrosion resistance, it is preferred that the Cu content range is controlled within 0.20% to 0.50%.
[0025] Mo: Mo is a recognized local corrosion resistant element. Whether in the metallic state or in the oxidized state, Mo in the rust layer can increase the resistivity of the rust layer, the densification degree of the rust layer, and thus improve the protectiveness of the rust layer. Mo and Cr also have a certain synergistic effect, which can promote the transformation process of alloy elements in the rust layer into corrosion-resistant products. In addition, Mo can also improve the hardenability and fatigue properties of steel. The present invention controls the range of Mo to be 0.25% to 0.35%.
[0026] V: V has a strong affinity with both C and N. The fine V (C, N) particles dispersed in the ferrite are the main way of strengthening by vanadium microalloying. The V (C, N) precipitates in the ferrite conform to the BN orientation relationship with the ferrite matrix, and maintain a coherent relationship with the ferrite matrix in the initial stage of uniform precipitation in the ferrite. Compared with other microalloying elements such as Nb and Ti, the carbides and nitrides of V have the smallest mismatch with the ferrite matrix, and the coherent relationship between the carbides and nitrides of V and the ferrite matrix can be maintained to a larger particle size, which is beneficial to improve the resistance of steel to fatigue crack initiation and expansion, and also improve the yield strength ratio, low temperature toughness and welding performance of steel. However, the V content should not be too high, otherwise it will reduce the toughness of the steel and be detrimental to the creep performance of the steel. The V content of the present invention is controlled at 0.020% to 0.039%.
[0027] N: An important strengthening element of the present invention, N exists in steel mainly in two states: free state and compound. The existence of the former is not good for the toughness of the steel plate, while the existence of the latter has a positive effect on the comprehensive performance of the steel plate. For V-containing steel, when there is a lack of N in the steel, most of the V does not fully exert its precipitation strengthening effect. Whether in austenite or in ferrite, the solubility of VN is much lower than that of VC. That is to say, the precipitation of VN in austenite and ferrite always has a greater chemical driving force. Therefore, as long as there is enough N element in the matrix, the greater chemical driving force will cause N-rich V (C, N) to precipitate preferentially in ferrite or austenite. N-containing steel not only eliminates the cost increase caused by degassing and refining to remove N during the steelmaking process, but also the increase of N in the steel can give full play to the role of V microalloying elements, saving the amount of alloying elements, thereby reducing production costs. The N content in the steel affects both the interphase precipitation and random precipitation process of V(C,N) in ferrite. N-rich V(C,N) has a greater chemical driving force when precipitating, so its nucleation rate during precipitation increases significantly. As the N content increases, the interlayer spacing and precipitate size of V(C,N) interphase precipitation decrease, the density of random precipitated particles in ferrite increases, and the size of precipitated particles decreases. Considering that the corrosion fatigue performance requirements of the steel of the present invention should take into account both the size and density of the precipitates, the range of N is controlled to be 0.017% to 0.025%.
[0028] Ca: Ca treatment is performed on molten steel to purify the molten steel. The Ca element can spheroidize the MnS inclusions and disperse their size, preventing the MnS inclusions from forming long strip plastic shapes during the rolling process, and forming dispersed spherical shapes, and refining the size of sulfide inclusions, inhibiting the hot brittleness of S, improving the impact toughness and Z-direction performance of the steel plate, and improving the anisotropy of the impact toughness of the steel plate. The amount of Ca added depends on the S content in the steel. If the Ca addition is too low, the treatment effect is not great; if the Ca addition is too high, the size of Ca(O,S) is too large, the brittleness is also increased, and it can become the starting point of the fracture crack, reducing the low-temperature toughness of the steel, while also reducing the purity of the steel and polluting the molten steel. The present invention controls the Ca element content to 0.002% to 0.005%.
[0029] P: P can segregate in the center of the slab and gather at the grain boundaries. It is an element that has an adverse effect on the low-temperature toughness, ductility and weldability of the steel plate. Although P has the effect of improving the corrosion resistance of the steel plate, it has a negative effect on the fatigue performance of the steel plate. Considering the requirements for the corrosion fatigue performance of the steel plate, P cannot be used as a characteristic element. The present invention requires that the P content be controlled to be no more than 0.01%.
[0030] S: S can combine with Mn in steel to form MnS inclusions. During hot rolling, MnS extends along the rolling direction to form a MnS inclusion belt along the rolling direction, which can easily become a crack source under long-term complex loads, seriously damaging the fatigue resistance, low-temperature impact toughness and Z-direction properties of the steel plate. Therefore, the present invention requires that the S content be controlled to be no higher than 0.002%.
[0031] Als: As a deoxidation and grain refinement element that must be added in the present invention, the added content is above 0.01%, but when it exceeds 0.08%, hot cracks of the ingot are easily generated, and the toughness of the steel is reduced. The Als content is controlled at 0.02% to 0.05%.
[0032] The second technical solution of the present invention is to provide a method for manufacturing high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance, including smelting, continuous casting, primary rolling, and secondary rolling;
[0033] (1) Smelting process: Smelting is carried out according to the composition range of the present invention. During converter smelting, the contents of elements such as C, Si, Mn, P, and S are adjusted to be within the range of the present invention, and other alloy components are added as required for smelting. The molten steel is refined and the contents of other alloy elements are adjusted to be within the range of the present invention. The molten steel after LF refining is subjected to RH treatment. During the RH treatment, nitrogen is blown throughout the process to ensure that the final N content of the steel is within the range of the present invention, and [H] ≤ 2.0 ppm and [O] ≤ 18 ppm in the steel are controlled. The LF and RH refining furnace treatments each require 20 to 40 minutes, the superheat of the molten steel in the middle package is ≤ 25°C, and the casting is protected throughout the process; the A, B, C, and D inclusions in the steel meet the requirements of: A ≤ 0.5, B ≤ 0.5, C ≤ 0.5, and D ≤ 0.5.
[0034] (2) One-pass rolling process: the primary heating temperature is 1150-1190°C, the rolling temperature is in the austenite recrystallization temperature zone of 1000-1060°C, and the average single-pass reduction rate is above 10%, in order to fully carry out the dynamic recrystallization process of austenite and refine the austenite grains; after the completion of the one-pass rolling, a rapid laminar cooling system with an average cooling rate of 10-20°C / s is used to rapidly cool the intermediate billet to room temperature, completing the austenitization pretreatment of the intermediate billet and obtaining a fine martensite / bainite structure;
[0035] (3) Secondary rolling process: The secondary heating intermediate billet is heated to 900-950℃ to re-austenize the intermediate billet. The pre-treatment structure after primary rolling and cooling is fine martensite / bainite structure. This non-stable structure has high internal energy storage. A large number of crystal defects such as dislocations and interfaces can provide a large number of recrystallization nucleation points during the secondary heating austenitization process, and a finer austenite structure can be obtained. On the other hand, the secondary heating is equivalent to the normalizing treatment, which is conducive to the uniform distribution of corrosion-resistant solid solution elements in the steel. Secondary rolling process: The secondary rolling temperature is 790-830℃ in the austenite / proeutectoid ferrite two-phase region, the average single-pass reduction rate reaches 15%-20%, and the final rolling temperature is 780-810℃. The purpose is to fully deform the austenite grains, provide energy storage and position for the phase deformation nucleus, increase the phase deformation nucleus rate, and further reduce the ferrite grains in the two-phase region, and finally achieve the purpose of grain refinement. After rolling, the steel plate needs to be straightened to improve the straightness of the steel plate and prevent the steel plate from warping during the cooling process. After straightening, the steel plate is immediately cooled to 750-800℃ and enters the rapid laminar cooling system with an average cooling rate of 5-10℃ / s. The return temperature is controlled at 590-640℃ to control the phase change structure and size. Then the steel plate is slowly cooled to room temperature, and the slow cooling time is ≥20h.
[0036] The beneficial effects of the present invention are:
[0037] (1) The present invention improves the purity of steel by controlling the sulfur and phosphorus content in pure steel smelting, and improves the steel quality by treating spheroidized inclusions with Ca. The chemical composition of the steel plate is rationally designed, and the steel is improved in seawater corrosion fatigue resistance by using low C content and adding Cr, Cu, and Mo corrosion-resistant characteristic elements in combination with VN microalloying. Cr, Cu, and Mo improve the corrosion resistance of steel, and Si and VN microalloying improve the fatigue resistance of steel. Through the synergistic effect of each element, the initiation and expansion of steel corrosion fatigue cracks are suppressed, so that the steel plate has excellent seawater corrosion fatigue resistance, elongation performance, and low-temperature impact performance.
[0038] (2) An innovative method of secondary heating rolling and controlled cooling is adopted. The intermediate billet is heated again after rapid cooling. The non-steady-state structure with high energy storage releases energy and provides a large number of nucleation sites during the re-austenitization process, which refines the austenite grain size of the intermediate billet. At the same time, it is beneficial to the good structure and alloy element uniformity of the second-stage rolled steel plate, which is beneficial to the improvement of the plasticity and toughness of the product, and provides a guarantee for the service safety of marine engineering.
[0039] (3) The steel plate prepared by the present invention has seawater corrosion fatigue resistance (corrosion fatigue life is more than 2.5 times that of conventional steel plates), high strength (yield strength ≥360MPa, tensile strength 490-630MPa), high ductility (elongation after fracture ≥33%) and low-temperature impact toughness (-40℃ Charpy impact energy ≥250J, zero plastic transition temperature (NDTT) ≤-50℃). The product thickness ranges from 20 to 50mm. The microstructure of the invention steel is mainly composed of ferrite + bainite, and the average ferrite grain size is 8.0-12.0μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a metallographic microstructure diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The present invention will be further described below by way of examples.
[0042] The embodiment of the present invention performs smelting, continuous casting, primary rolling and secondary rolling according to the component ratio of the technical solution;
[0043] One-step rolling process:
[0044] The heating temperature is 1150-1190°C, the rolling temperature is in the austenite recrystallization temperature zone of 1000-1060°C, and the average single-pass reduction rate is above 10%; after one rolling, the intermediate billet is quickly cooled to room temperature, and the cooling rate is 10-20°C / s;
[0045] Secondary rolling process:
[0046] The intermediate billet cooled to room temperature is heated up to 900-950℃ for the second time, the starting rolling temperature of the second rolling is 790-830℃, the average single-pass reduction rate reaches 15%-20%, and the final rolling temperature is 780-810℃; after straightening, the temperature of the steel plate is 750-800℃ and immediately enters the rapid laminar cooling system with an average cooling rate of 5-10℃ / s, the red-return temperature is controlled at 590-640℃, and then the steel plate is slowly cooled to room temperature.
[0047] Further, the smelting and continuous casting process: smelting is carried out according to the composition range of the present invention, and the contents of elements such as C, Si, Mn, P, S, etc. are adjusted during converter smelting to make their contents within the range of the present invention, and other alloy components are added as required for smelting; the molten steel is refined to adjust the contents of other alloy elements within the range of the present invention; the molten steel after LF refining is subjected to RH treatment, and nitrogen is blown throughout the RH treatment to ensure that the final N content of the steel is within the range of the present invention, and control [H]≤2.0ppm and [O]≤18ppm in the steel. The LF and RH refining furnace treatments each require 20 to 40 minutes, the superheat of the molten steel in the middle package is ≤25°C, and the casting is protected throughout the process; the A, B, C, and D inclusions in the steel meet the requirements of: A≤0.5, B≤0.5, C≤0.5, and D≤0.5.
[0048] The composition of the steel of the embodiment of the present invention and the comparative example is shown in Table 1. The main process parameters for smelting the steel of the embodiment of the present invention are shown in Table 2. The main process parameters for controlled rolling and controlled cooling of the steel of the embodiment of the present invention are shown in Table 3. The mechanical properties and NDTT temperature of the steel of the embodiment of the present invention are shown in Table 4. The mechanical properties and NDTT temperature of the steel of the embodiment of the present invention are shown in Table 4. Corrosion fatigue performance of the steel of the embodiment of the present invention and the comparative example.
[0049] Table 1 Composition of steel in the embodiments of the present invention and comparative examples (wt%)
[0050]
[0051] Note: P: ≤0.01%, S: ≤0.002%
[0052] Table 2 Main process parameters for steel smelting in the embodiment of the present invention
[0053]
[0054] Table 3 Main process parameters of controlled rolling and controlled cooling of steel in the embodiment of the present invention
[0055]
[0056] Table 4 Mechanical properties and NDTT temperature of steel in the embodiment of the present invention
[0057]
[0058] Table 5 Marine atmospheric corrosion resistance rate of steels in the embodiments of the present invention and comparative examples (g / m 2 h)
[0059] serial number Corrosion fatigue life (N) 1 639923 2 653373 3 667485 4 655021 5 674486 6 660614 7 665655 8 658367 Comparative Example 308671
[0060] Note: Anti-seawater corrosion fatigue performance test: refer to ISO 11782-Ⅰ-2017 "Corrosion of Metals and Alloys - Corrosion Fatigue Test Part 1 Cyclic Failure Test", and use the axial stress control method to determine the corrosion fatigue life curve. Stress ratio -1, peak stress 450MPa, loading frequency 1HZ. The corrosion fatigue corrosion solution is configured according to ASTM D1141-98 standard to simulate seawater, the pH value is adjusted with a dilute NaOH solution, and a 40mm thick EH36 steel plate is introduced as a comparative example. The corrosion fatigue performance of the embodiments of the present invention and the comparative example is tested to evaluate the anti-seawater corrosion fatigue performance of the steel plate.
[0061] The offshore steel plate produced by the technical solution disclosed in the present invention has a yield strength of ≥360MPa, a tensile strength of 490-630MPa, a Charpy impact energy of -40°C of ≥250J, a zero plastic transition temperature NDTT≤-50°C, a tensile elongation after fracture of ≥33%, a maximum elongation of ≥28%, and a steel plate thickness of 20-50mm; under the stress ratio of -1, a peak stress of 450MPa, and corrosion fatigue conditions of simulated seawater in which the corrosion solution is configured according to ASTM D1141-98 standard, the corrosion fatigue life is 63000-68000N.
[0062] In order to describe the present invention, the present invention is appropriately and fully illustrated by the examples in the above. The above implementation modes are only used to illustrate the present invention, but not to limit the present invention. Ordinary technicians in the relevant technical field can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made should be included in the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A high-strength marine engineering steel with high ductility and resistance to seawater corrosion fatigue, characterized in that: The composition of the steel is as follows by weight percentage: C: 0.057%, Si: 0.35%, Mn: 1.36%, Cr: 2.57%, Cu: 0.26%, V: 0.036%, N: 0.017%, Ca: 0.002%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.035%, and the rest is Fe and unavoidable impurities; the Charpy impact energy of the marine steel plate at -40°C is ≥ 250 J; under the stress ratio of -1, the peak stress is 450MPa, and the corrosion fatigue condition of the simulated seawater configured by the corrosion solution according to the ASTM D1141-98 standard, the corrosion fatigue life is 63000~68000N; The method for manufacturing a high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance comprises smelting, continuous casting, primary rolling and secondary rolling; One-step rolling process: The heating temperature is 1150~1190 ℃, the rolling temperature is 1000~1060 ℃ in the austenite recrystallization temperature zone, and the average single-pass reduction rate is above 10%; after one rolling, the intermediate billet is quickly cooled to room temperature, and the cooling rate is 10~20 ℃ / s; Secondary rolling process: The intermediate billet cooled to room temperature is heated up to 900~950℃ for the second time, the starting rolling temperature of the second rolling is 790~830℃, the average single-pass reduction rate reaches 15%~20%, and the final rolling temperature is 780~810℃; After straightening, the steel plate is immediately cooled to 750-800 °C and enters a rapid laminar cooling system with an average cooling rate of 5-10 °C / s. The return temperature is controlled at 590-640 °C, and then the steel plate is slowly cooled to room temperature.
2. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The marine engineering steel has a microstructure of ferrite+bainite, wherein the volume percentage of ferrite is 85%-95%, and the average grain size of ferrite is 8.0-12.0 μm.
3. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The offshore steel plate has a yield strength of ≥360 MPa, a tensile strength of 490-630 MPa, a zero plasticity transition temperature NDTT ≤-50°C, a tensile elongation after break of ≥33%, a maximum elongation of ≥28%, and a steel plate thickness of 20-50 mm.
4. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The smelting and continuous casting process comprises: smelting according to the composition of claim 1, adjusting the contents of C, Si, Mn, P and S elements in the converter smelting to make the contents within the range of claim 1, and adding other alloy components for smelting as required; refining the molten steel and adjusting the contents of other alloy elements within the range of claim 1; RH treatment of the molten steel after LF refining, blowing nitrogen throughout the RH treatment to ensure that the final N content of the steel is within the range of claim 1, and controlling [H]≤2.0ppm and [O]≤18ppm in the steel; LF and RH refining furnace treatments each require 20 to 40 minutes, the superheat of the molten steel in the tundish is ≤25°C, and the casting is protected throughout the process; the A, B, C and D inclusions in the steel meet the requirements of A≤0.5, B≤0.5, C≤0.5 and D≤0.
5.
5. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.059%, Si: 0.37%, Mn: 1.34%, Cr: 2.82%, Cu: 0.35%, V: 0.035%, N: 0.019%, Ca: 0.003%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.023%, and the rest is Fe and unavoidable impurities.
6. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.061%, Si: 0.36%, Mn: 1.28%, Cr: 3.35%, Cu: 0.44%, V: 0.033%, N: 0.025%, Ca: 0.003%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.034%, and the rest is Fe and unavoidable impurities.
7. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.064%, Si: 0.42%, Mn: 1.17%, Cr: 2.56%, Cu: 0.48%, V: 0.038%, N: 0.022%, Ca: 0.004%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.041%, and the rest is Fe and unavoidable impurities.
8. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.065%, Si: 0.39%, Mn: 1.25%, Cr: 3.48%, Cu: 0.40%, V: 0.030%, N: 0.021%, Ca: 0.005%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.029%, and the rest is Fe and unavoidable impurities.
9. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.053%, Si: 0.32%, Mn: 1.36%, Cr: 3.12%, Cu: 0.44%, V: 0.031%, N: 0.019%, Ca: 0.002%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.027%, and the rest is Fe and unavoidable impurities.
10. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.063%, Si: 0.43%, Mn: 1.26%, Cr: 3.03%, Cu: 0.39%, V: 0.034%, N: 0.017%, Ca: 0.003%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.043%, and the rest is Fe and unavoidable impurities.
11. The high-strength marine engineering steel with high ductility and seawater corrosion fatigue resistance according to claim 1, characterized in that: The composition of the steel is replaced, by weight percentage, as follows: C: 0.058%, Si: 0.51%, Mn: 1.33%, Cr: 2.99%, Cu: 0.47%, V: 0.031%, N: 0.012%, Ca: 0.004%, P: ≤ 0.01%, S: ≤ 0.002%, Als: 0.031%, and the rest is Fe and unavoidable impurities.
